Fight for Cancer Diseases using Natural Compounds and Their Semisynthetic Derivatives - Yehezkiel Steven Kurniawan; Kasta Gurning; Iksen Iksen; Ahmad Bikharudin (Bioactivities, 2024)
Cancer stands as one of the deadliest diseases afflicting contemporary human societies, encompassing over 100 distinct forms, including oral, salivary glands, oropharynx, nasopharynx, hypopharynx, colorectal, liver, pancreas, lung, skin, breast, cervix, ovary, prostate, kidney, brain, thyroid, and leukemia cancers. At the cellular level, the uncontrolled growth of cancerous cells can disrupt the body's normal functions. Chemotherapy, a widely recognized cancer treatment, utilizes anticancer agents to target specific cancer cell lines effectively. Natural compounds are favored for their compatibility with the body, minimal harm to healthy cells, and easy extraction from natural sources. These natural compounds and their derivatives hold promise for cancer therapy, boasting diverse structural and pharmacological characteristics. Additionally, chemical modifications can enhance their anticancer properties. This review explores the anticancer potential of terpenoids, flavonoids, alkaloids, xanthones, and epoxides, as well as elucidates their molecular mechanisms, such as their antiproliferative, apoptotic, antiangiogenic, and antimetastatic actions. Furthermore, the effect of the functional group on the anticancer activity through the structure-activity relationship will be discussed in detail, supported by molecular docking and molecular dynamic simulations. Combining experimental in vitro and in vivo assays with computational in silico assays significantly helps us understand how we shall fight cancer diseases in the modern era.